Using Digital Games to Learn Mathematics - What students think? - Su Ting Yong; Ian Harrison; Peter Gates (Serious Games Society, 2016)
The aim of this study was to explore how university foundation students perceive the use of digital games in learning mathematics. Data was collected using an online questionnaire and 209 foundation university students participated in this study.  The questionnaire was used to explore students' gaming experience and students' attitude towards mathematics learning with digital games.  It was found that most of the university foundation students liked to play different types of digital games.  Males preferred playing digital games in more traditional male genres namely sport, racing, shooter, action adventure, role play and strategy games.  As for females, they generally preferred playing puzzle and simulation games.  Astonishingly, the foundation students were not very positive towards the use of digital games in learning mathematics, and their attitude was essentially influenced by their mathematics interest.  Students with greater interest in mathematics were more likely to support the use of digital games in learning.